2017
DOI: 10.2478/tar-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Selected Aspects of the Low Level Automatic Taxi Control System Concept

Abstract: Taxiing of manned and remotely piloted aircraft is still performed by pilots without using a system of automatic control of direction and speed. Several reasons have emerged in recent years that make the automation of taxiing an important design challenge. The reasons are: decreased airport capacity due to the growing number of aircraft, poor ground operation conditions during poor visibility conditions, an increase in workload of pilots and air traffic controllers and the integration of simultaneous ground op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Taking into account previous research (Krawczyk et al, 2019), (Zajdel et al, 2017) on automatic taxiing direction control system for ultralight aircraft showed the ADRC algorithm to also be suitable for use in the said system in aircraft having significantly different parameters.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Taking into account previous research (Krawczyk et al, 2019), (Zajdel et al, 2017) on automatic taxiing direction control system for ultralight aircraft showed the ADRC algorithm to also be suitable for use in the said system in aircraft having significantly different parameters.…”
Section: Discussionmentioning
confidence: 93%
“…The control algorithm presented in this paper is a part of an automatic taxi control system (Zajdel et al, 2017). The proposed general structure of the system (Figure 4) is inspired by the structure of contemporary flight control systems.…”
Section: Automatic Taxiing Control Systemmentioning
confidence: 99%
“…The paper [6] delineated that the aircraft gas emissions directly have an effect on the Earth's system and health of humans. Natural issues have international treaties caused to be signed with the aim to reduce pollutants of fuels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the development of an automatic system for controlling the aircraft moving on the ground makes it possible to streamline this process, the effect of which should be an improvement of both efficiency and safety of the carriedout operation. Such a system should essentially consist of a layer responsible for creating a plan of taxiing and a low-level layer (Zajdel et al, 2017), the role of which would be its implementation occurring by controlling the aircraft direction and movement speed, in line with a predetermined time sequence of the performed manoeuvre. The paper will present an initial solution concept of one of the mentioned issues -related to a problem of automatic control of the aircraft movement direction in the taxiing phase.…”
Section: Introductionmentioning
confidence: 99%